'A Journey to the Heart of Matter': The Physical and Metaphysical Landscapes of CERN. (June 2015) - Jenkins, David; Schofield, John
Abstract : Archaeology is essentially about time and space. Physics also places emphasis on time and space, but extending further and deeper than the human dimension. Human life has existed on earth for some five million years, a thousand times shorter than the estimated age of the earth. Human interest in the motions of stars and planets extends back at least 10, 000 years, yet explorations of the universe remain limited. Archaeology and physics therefore appear to have much in common, and this paper considers ways in which landscape, as concept and entity, can helpfully unite these various interests, providing a lens through which searching and relevant questions can be addressed. Such questions concern, for example, methodologies for cultural understandings of Big Science and the coherence and distinctiveness of 'nuclear' landscapes, and how such landscapes can illuminate the place of our own perceptions of landscape within the wider 'ecosystem'. Our exploration is confined to a place where scientists from around the world cooperate for the benefit of all humanity. It is arguably the most important place on earth. That place is CERN.